2021
DOI: 10.3390/jcm10194583
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Inhibitors as Monotherapy for the First-Line Treatment of Non-Small-Cell Lung Cancer in PD-L1 Positive Patients: A Safety Data Network Meta-Analysis

Abstract: This network meta-analysis (NMA) evaluates the safety of first-line programmed death-ligand 1 (PD-L1) inhibitor monotherapy in advanced NSCLC patients compared to platinum-based chemotherapy. We also compared the risk of adverse events (AEs) according to programmed cell death-1 receptor (PD-1) or PD-L1 inhibitors therapy. To that end, we conducted a series of metanalyses (MAs) using data from six phase III clinical trials, including 4053 patients. Our results show a reduced risk of any grade treatment-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…Campelo et al found that PD-L1 inhibitors were associated with a lower risk of adverse events that led to treatment discontinuation than PD-1 inhibitors [43]. The use of PD-1 or PD-L1 inhibitors significantly increased the risk of serious immune-related adverse events in this study [43], but the incidences were very low. Meanwhile, the risk of non-serious adverse events did not increase.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Campelo et al found that PD-L1 inhibitors were associated with a lower risk of adverse events that led to treatment discontinuation than PD-1 inhibitors [43]. The use of PD-1 or PD-L1 inhibitors significantly increased the risk of serious immune-related adverse events in this study [43], but the incidences were very low. Meanwhile, the risk of non-serious adverse events did not increase.…”
Section: Discussionmentioning
confidence: 47%
“…Sonpavde et al's study showed that the incidence of grade 3 or higher adverse events was higher in the PD-1 inhibitors group compared with PD-L1 inhibitors [42]. Campelo et al found that PD-L1 inhibitors were associated with a lower risk of adverse events that led to treatment discontinuation than PD-1 inhibitors [43]. The use of PD-1 or PD-L1 inhibitors significantly increased the risk of serious immune-related adverse events in this study [43], but the incidences were very low.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, targeted therapy and perioperative immunotherapy may be accompanied by serious AEs that can lead to delay or cancellation of surgery, additional illness, and even death. The severity of AEs can range from asymptomatic, severe, to life threatening ( 29 ).…”
Section: Consensus 5: Perioperative Patient Managementmentioning
confidence: 99%
“…Application of immune checkpoint blockage (ICB) has significantly improved the prognosis of multiple tumors, but exerted limited effects on head and neck squamous cell carcinoma (HNSCC) because less than 30% of the patients got a better prognosis (Curran et al, 2010;Topalian et al, 2012;Seiwert et al, 2016;Clarke et al, 2021;García Campelo et al, 2021). To find out the HNSCC sub-populations susceptible to ICB therapy, various criteria have been proposed for HNSCC classification, by which HNSCC was classified into the enhanced and decreased immune subtypes with the immune-related genes (Cao et al, 2018), into the CD8 + high and CD8 + low subtypes with the density of infiltrating CD8 + T cells (Saloura et al, 2019), into the basal, mesenchymal, atypical, and classical subtypes with the integrated genomic characteristics (Walter et al, 2013), and even into the m6A high and m6A low subtypes with the N6methyladenosine (m6A) methylation levels on mRNAs (Yi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%